Transparent thermally conductive resin composition and transparent thermal conduction member
Patent Information
- Application Number
- JP2023142256
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-13
AI Technical Summary
【0010】 本発明によれば、透明性が高く、熱伝導性に優れる透明熱伝導性樹脂組成物及び透明熱伝導部材を提供することができる。
Smart Images

Figure 2025035302000001 
Figure 2025035302000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a transparent thermally conductive resin composition and a transparent thermally conductive member formed using the same. [Background technology]
[0002] In recent years, heat generated by power electronics technology used in hybrid devices, LED devices, etc. has become a problem. Recently, thermally conductive resins have been developed from the perspective of weight reduction, etc. In addition, for components around LED lighting and displays, ensuring transparency in addition to high thermal conductivity is also important.
[0003] Conventionally, materials in which thermally conductive fillers are added to resins have been used as thermally conductive resins, but there has been a problem that sufficient transparency cannot be obtained when the filler is highly filled to increase thermal conductivity. In response to such a problem, a resin composition in which a thermally conductive filler having an average particle size of 1 μm or more and 1000 μm or less is added to a resin (Patent Document 1), and a transparent thermally conductive composition in which a thermally conductive filler having an average particle size of 1 to 100 μm and a thermal conductivity of 2 W / m·K or more and a high refractive index filler having an average particle size of 1 to 100 nm and a refractive index of 1.8 or more are added to a resin (Patent Document 2) have been reported. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-35022 A [Patent Document 2] JP 2012-229317 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the technologies described in Patent Documents 1 and 2, micron (μm)-sized fillers are used as thermally conductive fillers, so even if the refractive indices of the resin and filler are matched at a specific wavelength, it is difficult to match the refractive indices over all wavelengths in the visible light range, and there is a limit to how much transparency can be achieved.
[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a transparent thermally conductive resin composition and a transparent thermally conductive member that are highly transparent and excellent in thermal conductivity. [Means for solving the problem]
[0007] As a result of extensive investigations, the present inventors have found that the above-mentioned problems can be solved by the following configuration, and have completed the present invention through further investigations based on this finding.
[0008] That is, a transparent thermally conductive resin composition according to one aspect of the present invention is a resin composition containing a resin and a thermally conductive filler, wherein the resin has a mass average molecular weight of 1,000 or more and less than 10,000 and a number of reactive groups of 1 or more and 4 or less, the average particle diameter of the thermally conductive filler is 200 nm or less, and the content of the thermally conductive filler relative to the total amount of the resin composition is 40% by weight or more and 80% by weight or less.
[0009] A transparent thermally conductive member according to another aspect of the present invention is characterized in that it is formed using the above-mentioned transparent thermally conductive resin composition. Effect of the Invention
[0010] According to the present invention, it is possible to provide a transparent thermally conductive resin composition and a transparent thermally conductive member which are highly transparent and excellent in thermal conductivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The transparent thermally conductive resin composition (hereinafter, simply referred to as "resin composition") of this embodiment is a resin composition containing a resin and a thermally conductive filler. The resin has a mass average molecular weight of 1000 or more and less than 10000, and a number of reactive groups of 1 or more and 4 or less. The average particle diameter of the thermally conductive filler is 200 nm or less, and the content of the thermally conductive filler relative to the total amount of the resin composition is 40% by weight or more and 80% by weight or less.
[0012] In order to increase the thermal conductivity using nano-sized fillers, a fairly high loading is required, so no attempt has been made to use nano-sized thermally conductive fillers. If the filler is loaded too highly, the hardness of the resin composition increases, and there is a problem that the resin film formed from the resin composition cracks. This problem becomes more pronounced as the thickness of the resin film increases.
[0013] According to the resin composition of the present embodiment, it is possible to achieve both high transparency and excellent thermal conductivity by using a nano-sized thermally conductive filler.
[0014] Specific embodiments of the present invention will be described below. However, the following embodiment is merely one of various embodiments of the present invention, and various modifications can be made depending on the design as long as the object of the present invention can be achieved.
[0015] (Transparent thermally conductive resin composition) First, the resin composition of the present embodiment will be described. As described above, the resin composition of the present embodiment contains a resin having a mass average molecular weight of 1000 or more and less than 10000 and a number of reactive groups of 1 or more and 4 or less, and a thermally conductive filler having an average particle size of 200 nm or less.
[0016] ·resin The resin used in this embodiment is not particularly limited as long as it has a mass average molecular weight of 1,000 or more and less than 10,000 and has 1 or more and 4 or less reactive groups.
[0017] If the mass average molecular weight is 10000 or more, the cohesive force between the resins becomes too strong when mixing the nano-sized thermally conductive filler described later, and the resins and the fillers coagulate with each other, making it difficult to obtain sufficient transparency. Also, if the molecular weight is less than 1000, the resin hardening speed becomes too fast, and film cracking may occur when forming a member. The more preferred mass average molecular weight of the resin of this embodiment is 1200 or more and less than 9000, and even more preferably 1400 or more and less than 8000.
[0018] If the number of reactive groups in the resin is less than 1, the resin will not cure sufficiently, resulting in tackiness (adhesiveness) and poor handleability, while if the number of reactive groups exceeds 4, the resin will cure too much and become hard, making it impossible to sufficiently fill the thermally conductive filler.
[0019] The resin of the present embodiment more preferably has 2 or more and 3 or less reactive groups.
[0020] In this embodiment, the "reactive group" is not particularly limited, and examples thereof include an acrylic group, a methacrylic group, an epoxy group, a vinyl group, an allyl group, an isocyanate group, an oxetane group, a styryl group, a carboxyl group, an alkoxysilyl group, a thiol group, etc. Among these, from the viewpoints of reactivity and storage stability, an acrylic group, a methacrylic group, a thiol group, and an epoxy group are preferable.
[0021] When the resin has two or more reactive groups, the reactive groups can be the same or different.
[0022] The type of resin in this embodiment can be any resin having a reactive group, and examples thereof include acrylic resin, methacrylic resin, urethane acrylate resin, epoxy resin, vinyl resin, allyl resin, urethane resin, oxetane resin, polystyrene resin, ester resin, silicone resin, enethiol resin, etc. Among these, from the viewpoints of transparency, flexibility, and compatibility with the thermally conductive filler, it is preferable to use acrylic resin, urethane acrylate resin, enethiol resin, epoxy resin, etc.
[0023] The content of the resin relative to the total amount of the resin components in the resin composition is preferably 50% by weight or more and 100% by weight or less. A content in this range provides advantages such as transparency, flexibility, and compatibility with the thermally conductive filler. The content is more preferably 60% by weight or more and 90% by weight or less.
[0024] Thermally conductive filler The thermally conductive filler contained in the resin composition of this embodiment can be any thermally conductive filler having an average particle size of 200 nm or less. By using a thermally conductive filler having an average particle size of 200 nm or less, high transparency can be ensured. In this embodiment, the "average particle size" refers to the particle size at an integrated value of 50% in the particle size distribution obtained by a laser diffraction / scattering method.
[0025] The average particle size is more preferably 100 nm or less, and further preferably 50 nm or less. Although there is no particular restriction on the lower limit, it is usually desirable for the average particle size to be 10 nm or more from the viewpoint of achieving a certain level of crystal growth as a filler.
[0026] The resin composition of the present embodiment may contain a single type of thermally conductive filler having the average particle size as described above, or may contain a combination of two or more types of thermally conductive fillers having average particle sizes in the above range.
[0027] Examples of the thermally conductive filler that can be used in the present embodiment include inorganic fillers, and examples of the inorganic fillers include oxide fillers, hydroxide fillers, carbide fillers, nitride fillers, etc. Among these, oxide fillers, hydroxide fillers, etc. are preferred from the viewpoint of obtaining high transparency.
[0028] Examples of oxide fillers include aluminum oxide (alumina), iron oxide, silicon oxide (silica), magnesium oxide, zinc oxide, beryllium oxide, and hydrates thereof (e.g., boehmite, etc.). Among these oxide fillers, alumina, boehmite, silica, etc. are preferably used from the viewpoint of obtaining high thermal conductivity and transparency. In addition, a preferred example of hydroxide filler is magnesium hydroxide, etc.
[0029] The shape of the thermally conductive filler of the present embodiment is not particularly limited, and may be spherical, cubic, polyhedral, plate-like, scaly, or amorphous such as wire-like. From the viewpoint of ease of dispersion, a spherical shape is preferable.
[0030] The thermally conductive filler of the present embodiment may be used as is, but may also be a filler that has been surface-treated with a silane coupling agent or the like, as necessary.
[0031] The above-mentioned thermally conductive fillers may be used alone or in combination of two or more kinds.
[0032] The content of the thermally conductive filler relative to the total amount of the resin composition is preferably 40% by weight or more and 80% by weight or less. If the content is in this range, there are advantages such as transparency, high thermal conductivity, and film cracking resistance. The content is more preferably 50% by weight or more and 80% by weight or less.
[0033] Thiol compounds The resin composition of the present embodiment preferably further contains a thiol compound in addition to the resin and the thermally conductive filler. By including a thiol compound in the resin composition, there is an advantage that the thermally conductive filler can be more highly filled.
[0034] The thiol compound is not particularly limited, and examples thereof include polyfunctional thiol compounds, monofunctional thiol compounds, etc. Among them, polyfunctional thiol compounds are preferably used from the viewpoint of imparting flexibility and making film cracking less likely to occur compared to acrylic resins having the same number of reactive groups.
[0035] The polyfunctional thiol compound is not particularly limited as long as it is a compound having two or more thiol groups in the molecule, and specific examples thereof include 1,4-bis(3-mercaptobutyryloxy)butane, trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptopropionate), dipentaerythritol hexakis(3-mercaptopropionate), tris[(3-mercaptopropionyloxy)ethyl]isocyanurate, pentaerythritol tetrakis(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, 1,3,5-tris(2-(3-sulfanylbutanoyloxy)ethyl)-1,3,5-triazinane-2,4,6-trione, and trimethylolpropane tris(3-mercaptobutyrate).
[0036] When the resin composition of the present embodiment contains a thiol compound, its content is preferably 5% by weight or more and 50% by weight or less based on the total amount of resin components in the resin composition. If the content is within this range, it has the advantage of being able to impart appropriate flexibility and making film cracking less likely to occur. The content is more preferably 10% by weight or more and 40% by weight or less.
[0037] Other additives The resin composition according to the present embodiment may contain additives (other components) other than the above-mentioned components as necessary within a range that does not impair the effects of the present invention. Specifically, for example, additives such as a photopolymerization initiator, an inorganic filler other than the thermally conductive filler, a flame retardant, an antifoaming agent, an antioxidant, a heat stabilizer, an antistatic agent, an ultraviolet absorber, a dye or pigment, a dispersant, and a lubricant may be further contained.
[0038] When the resin composition of the present embodiment contains a photopolymerization initiator, the content thereof is preferably 1% by weight or more and 5% by weight or less with respect to the total amount of the resin composition.
[0039] (Transparent heat conductive material) The transparent thermally conductive member of this embodiment is formed using the transparent thermally conductive resin composition. The thermal conductivity of the transparent thermally conductive member of this embodiment is 0.4 W / m·K or more. More preferably, it is 0.5 W / m·K or more, and further preferably, it is 0.6 W / m·K or more. The upper limit is not particularly limited, but is usually 5.0 W / m·K or less. In this embodiment, the thermal conductivity is a value measured by a thermal conductivity measuring device ("DynTIM Tester" manufactured by Mentor Graphics, Inc.).
[0040] The haze value of the transparent heat conductive member of this embodiment is 1.5% or less, more preferably 1.2% or less, and even more preferably 1.0% or less. There is no particular limitation on the lower limit, but it is usually 0.1% or more. In this embodiment, the haze value is a value measured using a haze meter ("NDH7000SP II" manufactured by Nippon Denshoku Industries Co., Ltd.) based on JIS K 7361-1:1997.
[0041] Furthermore, the visible transmittance of the transparent heat conductive member of this embodiment is 85% or more, more preferably 88% or more, and even more preferably 90% or more. There is no particular upper limit, but it is usually 95% or less. In this embodiment, the visible transmittance is a value measured using a haze meter ("NDH7000SP II" manufactured by Nippon Denshoku Industries Co., Ltd.) based on JIS K 7361-1:1997.
[0042] As described above, the transparent heat conductive member of the present embodiment is formed using the transparent heat conductive resin composition, and therefore has excellent transparency and heat conductivity, making it very useful for industrial use.
[0043] The shape of the transparent heat conductive member of the present embodiment is not particularly limited and can be appropriately determined depending on the application. For example, the transparent heat conductive member may be in a sheet shape, a plate shape, a film shape, a paste shape, a pellet shape, etc. From the viewpoint of handling, etc., the transparent heat conductive member is preferably in a sheet shape, a plate shape, or a sheet shape.
[0044] When the transparent heat conductive member of the present embodiment is in the form of a sheet, plate, or sheet, the thickness is not particularly limited, but is preferably 10 μm or more. Even when the transparent heat conductive member of the present embodiment has such a thickness, the transparent heat conductive member of the present embodiment does not crack and can ensure excellent transparency and thermal conductivity. When the thickness is 30 μm or more, the above effect can be more effectively exhibited. The upper limit of the thickness is not particularly limited, but is usually 2000 μm or less.
[0045] ·Manufacturing method The method for producing the transparent heat conductive member of the present embodiment is not particularly limited, and the member can be obtained by molding the resin composition of the present embodiment as described above by a known method.
[0046] Specifically, first, the transparent thermally conductive resin composition of the present embodiment is prepared by, for example, kneading the resin components and the thermally conductive filler in a predetermined ratio using a kneader, a batch mixer such as a Labo Plastomill, a roll kneader, or the like, and then cooling and solidifying the kneaded mixture, or by mixing the mixture in a dissolved or suspended state using a solvent.
[0047] Next, the obtained resin composition can be molded into a desired shape by various molding methods to obtain the transparent heat conductive member of the present embodiment. Examples of the molding method that can be used include injection molding, extrusion molding, compression molding, and blow molding.
[0048] As an example, a method for obtaining a sheet-shaped transparent heat conductive member will be described. First, the prepared transparent heat conductive resin composition of the present embodiment is applied to a substrate such as a release PET film to a desired thickness, and then cured by heating and UV irradiation. Then, the sheet-shaped transparent heat conductive member can be obtained by peeling it off from the release PET film.
[0049] ·Applications The transparent heat conductive member of the present embodiment can be used for various applications, and can be suitably used for, for example, LED lighting components, various display components, various sealing materials, smart windows, and the like.
[0050] As described above, this specification discloses various aspects of the technology, the main technologies of which are summarized below.
[0051] A transparent thermally conductive resin composition according to a first aspect of the present invention is a resin composition containing a resin and a thermally conductive filler, wherein the resin has a mass average molecular weight of 1,000 or more and less than 10,000 and a number of reactive groups of 1 or more and 4 or less, the average particle diameter of the thermally conductive filler is 200 nm or less, and the content of the thermally conductive filler relative to the total amount of the resin composition is 40% by weight or more and 80% by weight or less.
[0052] A transparent thermally conductive resin composition according to a second embodiment is the transparent thermally conductive resin composition of the first embodiment, wherein the resin composition further contains a thiol compound.
[0053] A transparent thermally conductive resin composition according to a third aspect is the transparent thermally conductive resin composition according to the first or second aspect, wherein the thermally conductive filler contains at least one oxide filler selected from alumina, boehmite, zinc oxide, silica, magnesium oxide, and magnesium hydroxide.
[0054] A transparent thermally conductive member according to a fourth aspect is formed using the transparent thermally conductive resin composition according to any one of the first to third aspects.
[0055] The transparent heat conductive member of the fifth aspect is the transparent heat conductive member of the fourth aspect, characterized in that it has a thermal conductivity of 0.4 W / m·K or more, a haze value of 1.5% or less, and a visible light transmittance of 85% or more.
[0056] A transparent heat conductive member according to a sixth aspect is the transparent heat conductive member of the fourth aspect, characterized in that it has a thickness of 10 μm or more.
[0057] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples. EXAMPLES
[0058] First, the various materials used in this example are as follows:
[0059] <Resin> Resin 1: Acrylic resin "APG-200" (tripropylene glycol diacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd., number of reactive groups: 2, mass average molecular weight: 300) Resin 2: Acrylic resin "UA-160TM" (urethane acrylate, manufactured by Shin-Nakamura Chemical Co., Ltd., number of reactive groups: 2, mass average molecular weight: 1600) Resin 3: Acrylic resin "UA-1100H" (urethane acrylate, manufactured by Shin-Nakamura Chemical Co., Ltd., number of reactive groups: 6, mass average molecular weight: 800) Resin 4: Acrylic resin "WFL-523" (DIC Corporation, reactive group number: 0, mass average molecular weight: 10,000)
[0060] <Thermal conductive filler> Thermally conductive filler 1: Alumina "ALMIBK30WT%-M115" (CIK Nanotech Co., Ltd., average particle size: 90 nm) Thermally conductive filler 2: Alumina "ALMIBK30WT%-N06" (CIK Nanotech Co., Ltd., average particle size: 100 nm) Thermally conductive filler 3: Alumina "NP-ALO-3" (EM Japan Co., Ltd., average particle size: 200 nm) Thermally conductive filler 4: Alumina "A2SM-CM4" (Admatechs Co., Ltd., average particle size: 400 nm) Thermally conductive filler 5: Alumina "AX3-10R" (Nippon Steel Chemical & Material Co., Ltd., average particle size: 3500 nm) Thermally conductive filler 6: Boehmite "NANOBYK-3630" (manufactured by BYK Japan Co., Ltd., average particle size: 30 nm)
[0061] <Thiol compounds> Multifunctional thiol compound "KarendsMT BD1" (manufactured by Resonac Co., Ltd., number of reactive groups: 2, mass average molecular weight: 294)
[0062] <Photopolymerization initiator> Photopolymerization initiator "Omnirad184" (manufactured by IGM Resins BV)
[0063] (Examples 1 to 8 and Comparative Examples 1 to 6) Method for preparing resin composition First, the resin, the thermally conductive filler, and other components were mixed to obtain the composition (parts by weight) shown in Tables 1 and 2, and the mixture containing the thermally conductive fillers 1 to 4 and 6 was shaken by hand to visually confirm that the inside was homogenized. For the mixture containing the thermally conductive filler 5, the mixture was dispersed using an ultrasonic homogenizer for 2 minutes to homogenize the mixture, thereby obtaining the resin compositions of each of the examples and comparative examples.
[0064] · Creating evaluation samples Next, the resin composition obtained above was applied onto a support (PET film) that had been subjected to a release treatment so that the thickness after drying would be 49 to 52 μm, and then dried at 80° C. for 60 minutes. Thereafter, the obtained dried product was UV-cured with a high-pressure mercury lamp (irradiation intensity 150 mW / cm 2 , cumulative light intensity 500mJ / cm 2 ) to obtain a sample for evaluation (transparent thermal conductive member).
[0065] (Evaluation test) ·Total light transmittance The total light transmittance of each sample of the examples and comparative examples was measured using a haze meter (NDH7000SP II manufactured by Nippon Denshoku Industries Co., Ltd.) based on JIS K 7361-1: 1997. In this test, a total light transmittance of 85% or more was considered to pass.
[0066] Haze value The haze value of each sample of the examples and comparative examples was measured using a haze meter (NDH7000SP II manufactured by Nippon Denshoku Industries Co., Ltd.) based on JIS K 7361-1: 1997. In this test, a haze value of 1.5% or less was considered to pass.
[0067] Thermal conductivity The thermal conductivity of each example and comparative example sample was measured using a thermal conductivity measuring device (DynTIM Tester manufactured by Mentor Graphics, Inc.) In this test, a sample with a thermal conductivity of 0.4 W / m·K or higher was considered to have passed the test.
[0068] The above results are summarized in Tables 1 and 2.
[0069] [Table 1]
[0070] [Table 2]
[0071] (Consideration) As is clear from the results in Tables 1 and 2, all of the transparent heat conductive members formed using the transparent heat conductive resin composition of the present embodiment were found to have excellent transparency and heat conductivity. In particular, the examples using the resin composition containing a thiol compound in addition to a resin having a mass average molecular weight of 1,000 or more and less than 10,000 and a number of reactive groups of 1 to 4 were excellent in balance between transparency and heat conductivity.
[0072] In contrast, the samples of the comparative examples did not reach the acceptable level in at least one of the characteristics of the haze value, total light transmittance, or thermal conductivity. Furthermore, the results of the comparative examples 1 and 2 showed that the amount of thermally conductive filler affected the balance between the haze value and the thermal conductivity. In addition, the results of the comparative example 3 confirmed that when the mass average molecular weight of the resin is less than 1000, the resin becomes too hard, causing film cracking, and it is not possible to mold a transparent thermally conductive member from the resin composition. On the other hand, the sample of the comparative example 6, in which the mass average molecular weight of the resin was too large, resulted in an increase in the haze value.
[0073] Furthermore, the results of Comparative Examples 4 and 5 show that when the average particle size of the thermally conductive filler exceeds 200 nm, sufficient transparency cannot be obtained.
Claims
1. A resin composition containing a resin and a thermally conductive filler, the resin has a mass average molecular weight of 1,000 or more and less than 10,000 and a number of reactive groups of 1 or more and 4 or less, The average particle size of the thermally conductive filler is 200 nm or less, A transparent thermally conductive resin composition, wherein the content of the thermally conductive filler relative to the total amount of the resin composition is 40% by weight or more and 80% by weight or less.
2. The transparent thermally conductive resin composition according to claim 1 , further comprising a thiol compound.
3. 2. The transparent thermally conductive resin composition according to claim 1, wherein the thermally conductive filler contains at least one oxide filler selected from the group consisting of alumina, boehmite, zinc oxide, silica, magnesium oxide, and magnesium hydroxide.
4. A transparent thermally conductive member formed using the transparent thermally conductive resin composition according to any one of claims 1 to 3.
5. 5. The transparent heat conductive member according to claim 4, which has a thermal conductivity of 0.4 W / m·K or more, a haze value of 1.5% or less, and a visible light transmittance of 85% or more.
6. The transparent heat conductive member according to claim 4 , having a thickness of 10 μm or more.
Citation Information
Patent Citations
Transparent thermoconductive composition
JP2012229317A
Transparent thermally conductive resin composition
JP2016035022A